STUDENTS’ PERCEPTONS OF GAMIFICATION APPROACH BY USING KAHOOT!: A SURVEY STUDY - Anidya Jihan Savira; Yosephin WL, Maria; Cicik Shopia B, Theresia; Prihadi, Agus (English Study Program University of Pasir Pengaraian, 2024)
Technological innovation has created various learning models and tools that can increase the effectiveness of the learning process. There are a wide variety of learning software and platforms designed to support teachers in their teaching process and help them create a sustainable learning environment. Research has shown that infusion of 'gamification' software can influence and improve student learning outcomes and create a positive learning environment. This article reports a survey study conducted among 32 students from 8D SMP N 36 Semarang who had experience using Kahoot! in the learning process. This study used the closed-ended questionnaire consisting of 10 statements regarding the students' perceptions for gamification approach and the use of Kahoot!. The questionnaire of the Likert Scale consists of 4 (four) alternative points, specifically: Strongly Agree (SA), Agree (A), Disagree (D), and Strongly Disagree (SD). The four-choice scales were used to force respondents to choose one of the points because the points